The role of the International Court of Justice and the International Court of the Sea in settling maritime disputes and developing international law of the sea - Cheriet, Souheila (Journal of Human Sciences, 2023)
International disputes in general and maritime disputes in particular are among the most dangerous and widespread disputes in recent times, and the continuation of such disputes not only affects relations between neighboring countries, but can also turn into a military confrontation that inevitably leads to a threat to international peace and security, and with the escalation of The frequency of these disputes and the damages they cause have become necessary to settle them by peaceful means, and this is what was stipulated in Article 33 of the Charter of the United Nations.The settlement of these disputes by peaceful means is the aim of the international community as a whole, with the aim of preventing the use of force and establishing the principles of peace and justice. They contributed significantly to the development of international law of the sea by resolving many disputes and maritime issues.